Circulating fatty acids in relation to alcohol consumption: Cross-sectional results from a cohort of 60-year-old men and women. Issue 6 (December 2018) - Laguzzi, F.; Risérus, U.; Marklund, M.; Vikström, M.; Sjögren, P.; Gigante, B.; Alsharari, Z.D.; Hellénius, M.-L.; Cederholm, T.; Frumento, P.; de Faire, U.; Leander, K.
Summary: Background & aims: Alcohol consumption is considered to affect circulating fatty acids (FAs) but knowledge about specific associations is limited. We aimed to assess the relation between alcohol consumption and serum FAs in 60-year-old Swedish men and women. Methods: In a random sample of 1917 men and 2058 women residing in Stockholm county, cross-sectional associations between different categories of alcohol consumption and FAs were assessed using linear regression; β1 coefficients with 95% confidence interval (CI) were calculated. Self-reported alcohol consumption was categorized as none, low (≤9.9 g/day) (reference), moderate (10−29.9 g/day) and high (≥30 g/day). Moderate alcohol consumption was further subdivided into consumption of beer, wine, liquor and their combinations. Thirteen serum cholesterol ester FAs were measured by gas chromatography and individual FAs were expressed as percentage of total FAs. Results: Increasing alcohol consumption was associated to linear increase of saturated myristic acid, monounsaturated FAs and n-6 polyunsaturated (PUFA) arachidonic acid, whereas linear decrease was noted for saturated pentadecanoic acid and for n-6 PUFA linoleic acid. With non-linear associations, increasing alcohol consumption also associated to decreased saturated stearic acid, n-6 PUFA dihomo-gamma-linolenic acid, and n-3 PUFA docosahexaenoic acid and increased saturated palmitic acid, n-6 PUFA gamma-linolenic acid and n-3 PUFA eicosapentaenoic acid. Among types of beverages, wine consumption was associated with n-6 PUFA arachidonic acid (β1 0.59; 95% CI: 0.30;0.88) and the n-3 PUFAs eicosapentaenoic acid (β1 0.54; 95% CI: 0.30;0.78), and docosahexaenoic acid (β1 0.06; 95% CI: 0.00;0.12). Conclusions: These findings may give important basis for further investigations to better understand biological mechanisms behind the dose-dependent associations between alcohol consumption and health outcomes observed in many previous studies.